Ground floor, David Sassoon Clock Tower - Ghosh, Ayan (2023)
The ground floor of the clock tower is 12 square feet in area and open on all sides. A path leading from Jijamata Bhonsle Udyan is the entry point, and it exits on BR Ambedkar Road, though a boundary wall separates the road and the tower. The other two entrances have balustrades. The entrances are flanked on either side by decorative fluted colonettes.